A Smart Procedure for the Femtosecond Laser-Based Fabrication of a Polymeric Lab-on-a-Chip for Capturing Tumor Cell. (October 2021) - Volpe, Annalisa; Krishnan, Udith; Chiriacò, Maria Serena; Primiceri, Elisabetta; Ancona, Antonio; Ferrara, Francesco
Abstract: Rapid prototyping methods for the design and fabrication of polymeric labs-on-a-chip are on the rise, as they allow high degrees of precision and flexibility. For example, a microfluidic platform may require an optimization phase in which it could be necessary to continuously modify the architecture and geometry; however, this is only possible if easy, controllable fabrication methods and low-cost materials are available. In this paper, we describe the realization process of a microfluidic tool, from the computer-aided design (CAD) to the proof-of-concept application as a capture device for circulating tumor cells (CTCs). The entire platform was realized in polymethyl methacrylate (PMMA), combining femtosecond (fs) laser and micromilling fabrication technologies. The multilayer device was assembled through a facile and low-cost solvent-assisted method. A serpentine microchannel was then directly biofunctionalized by immobilizing capture probes able to distinguish cancer from non-cancer cells without labeling. The low material costs, customizable methods, and biological application of the realized platform make it a suitable model for industrial exploitation and applications at the point of care.